2010
DOI: 10.1590/s0100-204x2010000800017
|View full text |Cite
|
Sign up to set email alerts
|

Relações solo-paisagem no Quadrilátero Ferrífero em Minas Gerais

Abstract: Resumo -O objetivo deste trabalho foi caracterizar os solos de uma área representativa do Quadrilátro Ferrífero, em Minas Gerais, e avaliar suas relações com os principais componentes do meio natural. Sete unidades de paisagem (pedoambientes) distintas foram identificadas -Depressão do Paraopeba, Serras Itabiríticas, Platô da Moeda, Vale do Rio das Velhas, Gandarela, Vale do Conceição e Serra do Caraça -, cujos aspectos relacionados a solos em suas interrelações com os componentes do meio natural foram descrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 6 publications
2
15
0
11
Order By: Relevance
“…In this study, chemical analysis showed that the lowest value was 124.7 mg dm -³ . This result corroborates the soil characterization made by Carvalho Filho et al (2010) in this region, which describes the soils of the inner face of the Serra da Moeda as shallow and generally very stony that are derived from itabirite, with great iron concentration.…”
Section: Chemical and Physical Analysis Of Soilssupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, chemical analysis showed that the lowest value was 124.7 mg dm -³ . This result corroborates the soil characterization made by Carvalho Filho et al (2010) in this region, which describes the soils of the inner face of the Serra da Moeda as shallow and generally very stony that are derived from itabirite, with great iron concentration.…”
Section: Chemical and Physical Analysis Of Soilssupporting
confidence: 89%
“…The landscape of this environment is currently composed of fragments of Brazilian environmental hotspots, the Brazilian neotropical savanna (Cerrado) and the Atlantic Forest, which have been intensely transformed by human activities, with emphasis on urbanization and mining, generating impacts such as soil removal and consequent loss of vegetation cover (Jacobi and Carmo, 2008). Soils in this region are mainly ferruginous and generally of low fertility, acidic, and shallow; this has a considerable effect on the vegetation cover, which is composed of plants adapted to these peculiar conditions in the areas of ironstone outcrops (Costa, 2007;Carvalho Filho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One of these areas in the central part of Minas Gerais is known as the Quadrilátero Ferrífero, which is of great historical-cultural and economic importance due to iron ore extraction (Carvalho Filho;Curi;Shinzato, 2010). However, although the extraction of Fe is economically important, iron mining brings about changes in the landscape, with impacts on plant cover, on soil biodiversity, and, consequently, on the biogeochemical cycles of the elements (Siqueira et al, 2007;Xing et al, 2015) since the process of opening mining pits involves removing soil over the ore (which is sterile) and depositing it in other locations, forming piles.…”
Section: Introductionmentioning
confidence: 99%
“…As médias anuais de precipitação estão entre 1.000-1.500 mm e as de temperatura variam entre 19-22 ºC (SEA, 1980). A região marca a transição entre o Cerrado e a Mata Atlântica, apresentando grande diversidade e complexidade estrutural de ambientes e tipos fi tofi sionômicos, com destaque para as matas de galeria, florestas semideciduais, matas de candeia, campo cerrado, campos rupestres e de altitude (CARVALHO FILHO et al, 2010).…”
Section: A áRea De Estudounclassified